2006
DOI: 10.1128/aem.00791-06
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Salmonella enterica Serovar Newport in Manure and Manure-Amended Soils

Abstract: Salmonella enterica serovar Newport has undergone a rapid epidemic spread in dairy cattle. This provides an efficient mechanism for pathogen amplification and dissemination into the environment through manure spreading on agricultural land. The objective of this study was to determine the survival characteristics of Salmonella serovar Newport in manure and manure-amended soils where the pathogen may be amplified. A multidrug-resistant (MDR) Salmonella serovar Newport strain and a drug-susceptible (DS) strain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(131 citation statements)
references
References 22 publications
8
119
1
3
Order By: Relevance
“…According to You et al (2006), the environment of the soil does not create optimum conditions for existence of the fecal bacteria. The research performed by Yamahara et al (2012) shows that some of the fecal bacteria multiply inside the soil and adsorb on the particle of the soil or move deeper into the soil.…”
Section: Microbiological Parametersmentioning
confidence: 99%
“…According to You et al (2006), the environment of the soil does not create optimum conditions for existence of the fecal bacteria. The research performed by Yamahara et al (2012) shows that some of the fecal bacteria multiply inside the soil and adsorb on the particle of the soil or move deeper into the soil.…”
Section: Microbiological Parametersmentioning
confidence: 99%
“…Salmonella spp. have been reported to survive from a few days up to 332 days in manure-amended soils (Holley et al, 2006;Islam et al, 2004;You et al, 2006) and S. enterica is known to survive for five weeks in fallow soil (Nicholson et al, 2005;Jensen et al, 2006). In addition, bacteria, which are often found in vegetables and are associated with foodborne outt.…”
Section: Discussionmentioning
confidence: 99%
“…You et al (2006) studied the inactivation of a multidrug resistant Salmonella serovar Newport strain and a drug susceptible strain in dairy manure and found that the Salmonella count increased during the first 3 d incubation. Subsequently, the Salmonella levels decreased until 35 d incubation.…”
Section: St Inactivation In Dairy Wastewater At Mesophilic Environmentmentioning
confidence: 99%
“…The recycling of dairy wastewater (which is likely to have elevated bacterial loads and is stored in ponds) for cleaning the barns is a normal practice which also poses the risk of recirculation of pathogens. Previous research reported that pathogens can survive in dairy wastewater for extended periods of time (Kearney et al 1993;Wang et al 1996;Heinonen-Tanski et al 1998;You et al 2006). …”
Section: Introductionmentioning
confidence: 99%